MEMBUMIKAN ISLAM RAHMAH LI AL-ALAMIN; Studi Gerakan Dialog dan Toleransi M. Fethullah Gulen - Moh. Samsudin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2013)
Islam came to bring the vision of blessing for the universe. The western world view, such a mission is just a cliche. SoGülen developed religious patterns basedonsocial movementguided by the spirit of love for all. The Islamic teachings were reconstructed so that could be articulated with the International world through the tolerance teachings. It was quite effective, proven religious movement embodied in the medium of dialogue and pluralisteducational activities, International worldprovided appreciation. Thusit appearedthe friendly face of Islam and love peace as a form of vision Rahmah li al-Alamin